Diffusion tensor distribution imaging of an in vivo mouse brain at ultrahigh magnetic field by spatiotemporal encoding. (19th August 2020) - Yon, Maxime; de Almeida Martins, João P.; Bao, Qingjia; Budde, Matthew D.; Frydman, Lucio; Topgaard, Daniel
Abstract : Diffusion tensor distribution (DTD) imaging builds on principles from diffusion, solid‐state and low‐field NMR spectroscopies, to quantify the contents of heterogeneous voxels as nonparametric distributions, with tensor "size", "shape" and orientation having direct relations to corresponding microstructural properties of biological tissues. The approach requires the acquisition of multiple images as a function of the magnitude, shape and direction of the diffusion‐encoding gradients, leading to long acquisition times unless fast image read‐out techniques like EPI are employed. While in previous in vivo human brain studies performed at 3 T this proved a viable option, porting these measurements to very high magnetic fields and/or to heterogeneous organs induces B 0 ‐ and B 1 ‐inhomogeneity artifacts that challenge the limits of EPI. To overcome such challenges, we demonstrate here that high spatial resolution DTD of mouse brain can be carried out at 15.2 T with a surface‐cryoprobe, by relying on SPatiotemporal ENcoding (SPEN) imaging sequences. These new acquisition and data‐processing protocols are demonstrated with measurements on in vivo mouse brain, and validated with synthetic phantoms designed to mimic the diffusion properties of white matter, gray matter and cerebrospinal fluid. While still in need of full extensions to 3D mappings and of scanning additional animals to extract more general physiological conclusions, this work represents another step towards the model‐free, noninvasive in vivo characterization of tissue microstructure and heterogeneity in animal models, at ≈0.1 mm resolutions. Abstract : Diffusion tensor distribution (DTD) imaging allows to quantify the heterogeneity of tissues in terms of local "sizes", "shapes" and orientations, which are in turn directly related to the microstructural properties of biological tissues. Here, a high‐definition DTD analysis of a mouse brain is presented, carried out at 15.2 T with a surface‐cryoprobe and relying on a SPatiotemporal ENcoding (SPEN) imaging sequence. These results enabled the model‐free, noninvasive characterization of tissue microstructure and heterogeneity in live animals, at ≈0.1 mm resolutions.